Effectiveness of Virtual Laboratory Utilization in Improving Students' Science Process Skills - Abdul Kadir (Ta'dib, 2023)
The aim of this study is to determine the effectiveness of using a virtual laboratory. This research was carried out at SMAN 1 and MAN 1 Kolaka for 3 (three) months. The type of research is quantitative with an experimental method with a pretest-posttest control group design. The research population was students of class The instrument is a test of students' science process skills. Data analysis techniques were carried out descriptively and inferentially. The research results reported that there was an increase in student learning outcomes and a positive impact on the science process skills of students at SMAN 1 Kolaka and MAN 1 Kolaka after implementing a PhET-based virtual laboratory. Thus, the application of the Science-Physics learning model through a PhET-based virtual laboratory is effective in improving the science process skills of students at SMAN 1 Kolaka and MAN 1 Kolaka. This research gives the impression that laboratory use is not actually the only equipment used to carry out experiments. However, laboratories have developed so that students and teachers can carry out experiments through virtual laboratories at affordable costs.